Modeling a grid‐connected concentrator photovoltaic system. (6th February 2014) - Strobach, Ehud; Faiman, David; Kabalo, Shlomo; Bokobza, Dov; Melnichak, Vladimir; Gombert, Andreas; Gerstmaier, Tobias; Röttger, Michael
Abstract A six‐parameter formula is proposed for describing the hourly alternating current performance of a grid‐connected, passively cooled concentrator photovoltaic (CPV) system. These system parameters all have physical meanings, and techniques are described for deriving their numerical values. The predictions of the model are compared with the measured output of a Soitec CPV system at Sede Boqer and found to be accurate to approximately ± 5% at all times of the year. The model should also be valid for systems of similar construction operated in different climates from the system studied here, and also for passively cooled CPV systems of different designs provided that suitable numerical values are determined for their system parameters. Another possible use of the model is as a guide for tailoring CPV cell architecture to the particular spectral conditions of the locations in which they will operate. Attention is drawn to the fact that the numerical values of some of the system parameters are found to depend upon the time binning employed for the data. An explanation is given for this phenomenon, which is also found to occur for non‐concentrating photovoltaic panels. Copyright © 2014 John Wiley & Sons, Ltd.